Genotyping of Coxiella burnetii in sheep and goat abortion samples - Chochlakis, Dimosthenis (2019)
Background: Q fever, caused by Coxiella burnetii, is a zoonosis that presents a worldwide distribution and affects both humans and animals. The route of dispersal of the pathogen by ruminants into the environment usually involves stages of abortion and parturition, nevertheless the agent can, also, be detected in other animal samples. Therefore it is considered as important in terms of proper diagnosis, as well as, for epidemiology and surveillance purposes, to genotype the pathogen. The aim of the current study was to investigate the presence of different genotypes of the agent in animals that had suffered from abortion during a two-year survey in Greece. Results: Sixty nine tissue samples (37 stomach contents, 11 liver samples, 21 cotyledons) were collected from 59 abortion cases in sheep (N = 45) and goats (N = 14) from 65 farms at eight different areas of Greece. Samples were screened by qPCR and positive ones were further genotyped using a 10-locus multiple loci (ms 1, 3, 7, 12, 20, 21, 22, 26, 30 and 36) variable number of tandem repeat analysis (MLVA) method. Three genotypes were identified in sheep (A, B, C). Samples representing each of the obtained MLVA profile were further used for MST genotyping. Ten spacers (Cox 2, 5, 6, 18, 20, 22, 37, 51, 56 and 57) were amplified. A close relatedness among the identified MLVA genotypes was confirmed since they all belonged to MST group 32. Conclusions: The current study introduces into the aspect of genotyping of C. burnetii in Greece. Further studies are needed to explore the presence of more genotypes, to associate the genotypes circulating in the animal and tick population with those causing human disease in order to further expand on the epidemiological aspects of the pathogen.